Frequency of Union in Open Tibia Fractures treated with Unreamed Intramedullary Interlocking Nails (Journal of Pakistan Orthopaedic Association, 2020)
Objectives: To determine the frequency of union in open tibia fractures treated with unreamed interlocking intramedullary tibial nails.Methods: This descriptive study was conducted in Department of Orthopaedics and Spine Surgery Ghurki Trust Teaching Hospital Lahore from 15th February 2018 to 14th November 2019. All patients with open  diaphyseal tibial fractures fulfilling the inclusion criteria were fixed with unreamed interlocking intramedullary nails. Patients were followed up at intervals for nine months and clinical and radiological union was noted at final follow up visit.Results: The total number of patients in our study were 214.The mean age of our study participant was 45.47 ± 9.65 years.Male patients were 133(62.15%) and female 88(37.85%).Majority(87.85%,n=188) patients revealed clinical and radiological union at nine months while 26(12.1%) patients had non union.No major complication noted.Conclusion: High union rate had been achieved in open tibial fractures treated with unreamed interlocking nails.Unreamed interlocking nails therefore, can be used to treat Gustilo Anderson type I and type II diaphyseal fractures of tibia with good results.